Urban solid waste management and quality of life in Peru in the Latin American context: a systematic review (2020-2025) - Herrera Marca, Juan (2026)
Urban solid waste management represents a challenge for protecting the environment and improving population well-being in Latin America. This study analyzed how urban solid waste management can affect quality of life in Peru and other countries in the region between 2020 and 2025. A systematic review of articles was conducted following the PRISMA protocol, using the Scopus, SciELO, and ScienceDirect databases and applying inclusion criteria based on language and year of publication. Of a total of 110 articles identified, 30 studies corresponding to six Latin American countries were selected. The results indicate that insufficient available infrastructure, governance problems, and lack of funding affect service efficiency and social well-being. In addition, innovative experiences were identified, such as community composting, biodigestion, and environmental education programs. Finally, it is concluded that proper solid waste management contributes to sustainable development.